2011
DOI: 10.1088/0957-4484/22/28/285605
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Ge quantum dots embedded in SiO2matrix synthesized by plasma immersion ion implantation

Abstract: A new plasma process, i.e. a combination of plasma immersion ion implantation and deposition (PIII&D) and high power impulse magnetron sputtering (HiPIMS), was developed to implant non-gaseous ions into material surfaces. The new process has the great advantage that thin film deposition and non-gaseous ion implantation can be achieved in a single plasma chamber. In this study, Ge ions were successfully implanted into SiO(2) thin film, which resulted in uniformly and homogeneously distributed crystalline Ge qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Due to the confinement of carriers in three dimensions, semiconductor quantum dots (QDs) are endowed with many interesting physical properties, such as the quantum size effect, the phonon bottleneck effect, the quantum tunneling effect, the Coulomb blockade effect, and the quantum hall effect-properties that have made QDs the most promising of all candidates for developing novel electronic and optoelectronic devices [1][2][3][4][5]. At the same time, the carrier capture time in QDs is much shorter than that in general quantum wells and defects [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the confinement of carriers in three dimensions, semiconductor quantum dots (QDs) are endowed with many interesting physical properties, such as the quantum size effect, the phonon bottleneck effect, the quantum tunneling effect, the Coulomb blockade effect, and the quantum hall effect-properties that have made QDs the most promising of all candidates for developing novel electronic and optoelectronic devices [1][2][3][4][5]. At the same time, the carrier capture time in QDs is much shorter than that in general quantum wells and defects [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Ge QDs gained a renewed scientific interest over Si QDs, thanks to lower fabrication temperatures, higher absorption coefficient, and larger exciton Bohr radius ($24 nm). [5][6][7][8][9][10] Actually, Ge QDs embedded in SiO 2 have been already used in high-efficiency light detection devices, 11 showing also good tunneling features in resonant tunneling diodes. 12 Even if Ge QDs seem promising candidates as light harvesters, the photon absorption mechanism needs to be further exploited, especially for what concerns the embedding matrix.…”
mentioning
confidence: 99%
“…[5][6][7][8]12,[15][16][17][18] Since it was shown that the fabrication techniques 19 and undesired Ge-O interaction 9 can affect the optical properties, we induced the formation of Ge NCs by implanting Ge ions in Si 3 N 4 or SiO 2 matrices and annealing. Implant energy (100 keV) and fluences (2.9À9.6 Â 10 16 Ge ions/cm 2 ) were chosen to induce the NC precipitation within 90 nm from the surface.…”
mentioning
confidence: 99%
“…In order to overcome these limitations, it has been proposed to use nanocrystals (NCs) as charge storage elements embedded in the gate oxide of a field-effect transistor. [1][2][3][4][5][6] Various processes have been developed to elaborate silicon (Si) or germanium (Ge) NCs, including self-assembly, 7-9 precipitation, 10 ion implantation, [11][12][13][14] and annealing. [15][16][17] Si and Ge NCs for which the local physical properties govern their electronic response have recently been fabricated.…”
mentioning
confidence: 99%